Alcohol‐induced cognitive deficits are associated with decreased circulating levels of the neurotrophin BDNF in humans and rats. (12th September 2018) - Silva‐Peña, Daniel; García‐Marchena, Nuria; Alén, Francisco; Araos, Pedro; Rivera, Patricia; Vargas, Antonio; García‐Fernández, María Inmaculada; Martín‐Velasco, Ana Isabel; Villanúa, María Ángeles; Castilla‐Ortega, Estela; Santín, Luis; Pavón, Francisco Javier; et al.
Abstract: Chronic alcohol consumption is associated with neurocognitive and memory deficits, dramatically affecting plasticity and connectivity, with maximal expression as dementia. Neurotrophic factors may contribute to alcohol‐related cognitive decline. For further investigation, a cross‐sectional study was performed to evaluate the association of cognitive impairment, by using frontal assessment battery, and memory loss, using memory failures everyday, with the circulating levels of the neurotrophin brain‐derived neurotrophic factor (BDNF) and neurotrophin 3 (NT‐3) in abstinent subjects with alcohol use disorders (AUDs, N = 58, average of 17.9 years of problematic use and 4.3 months of abstinence) compared with healthy control subjects ( N = 22). This association was also explored in a pre‐clinical model of adolescent rats chronically exposed to alcohol up to adulthood ( 77 days old) in a three‐bottle free‐choice (5–10–20 percent), repeated abstinence and relapse paradigm. AUD subjects had low educational level and cognitive impairment associated with teenage consumption and lower circulating levels of BDNF and NT‐3. Only BDNF concentration showed a positive correlation with frontal assessment battery in AUD patients. In the ethanol‐exposed rats, the plasma levels of BDNF and NT‐3 were also decreased, and a negative correlation between hippocampal Bdnf mRNA levels and recognition memory was found. The ethanol‐exposed rat hippocampus showed a decrease in the mRNA levels of neurotrophic ( Bdnf and Ntf‐3 ) and neurogenic ( Mki67, Sox2, Dcx, Ncam1 and Calb1 ) factors, associated to a deactivation of the neurogenic regulator mitogen‐activated protein kinase extracellular signal‐regulated kinase. Results suggest a relevant role of BDNF/extracellular signal‐regulated kinase 2 signaling in alcohol‐induced cognitive impairment and suggest that early alcohol exposure‐derived effects on cognition are associated with neurotrophin signaling deficits. Abstract : There was a negative correlation between plasma BDNF and cognition deficit in alcohol patients. Hippocampal Bdnf levels and recognition memory negatively correlated in alcohol‐exposed rats during adolescence, an effect that was associated with a neurogenic regulator ERK2 deactivation. Early alcohol‐induced cognitive decline is related to BDNF signaling deficits.